“ THEJAKARTAPOST” AS A DRIVING FORCE OF LITERACY TO ENHANCE STUDENTS’ ENGLISH SKILLS - Yen Polisda (English Language Teaching and Research, 2017)
This article aims at facilitating literacy empowerment for Indonesian students learning English by utilizing one of Indonesian English Newspapers, “TheJakartaPost” as a driving force of literacy. The rationale is that  “TheJakartaPost” newspapers have a built-in capacity to motivate students to be literate readers due to real life contexts of Indonesia, up-to date information, and frequently used words. This, at the end, will enhance their English skills. Some research found out that the main medium used by English teachers to empower literacy is a number of books. However, a number of research reveal that Indonesian students are poor in literacy. Of course, this reaseach finding correlates to poor litaracy in English which leads to low ability in English skills. Therefore, this article discusses pedagogical reasons of using “TheJakartaPost” as a driving force of literacy and suggested teaching procedures. It is expected that English teachers use “TheJakartaPost” as one of the alternatives to help students literate for enhancing their English skills. Keywords:  TheJakartaPost: Literacy; English Skills